Atomic interferometer based on optical tweezers - Jonathan Nemirovsky; Rafi Weill; Ilan Meltzer; Yoav Sagi (Physical Review Research, 2023)
Atomic interferometers measure forces and acceleration with exceptional precision. The conventional approach to atomic interferometry is to launch an atomic cloud into a ballistic trajectory and perform the wave-packet splitting in momentum space by Raman transitions. This places severe constraints on the possible atomic trajectory, positioning accuracy, and probing duration. Here, we propose and analyze an alternative atomic interferometer that uses micro-optical traps (optical tweezers) to manipulate and control the motion of atoms. This interferometer allows long probing time, submicrometer positioning accuracy, and utmost flexibility in the shaping of the atomic trajectory. The cornerstone of the tweezer interferometer consists of the coherent atomic splitting and combining schemes. We present two adiabatic schemes with two or three tweezers that are robust in the presence of experimental imperfections and work simultaneously with many vibrational states. The latter property allows for multiatom interferometry in a single run. We also highlight the advantage of using fermionic atoms to obtain single-atom occupation of vibrational states and to eliminate mean-field shifts. We examine the impact of tweezer intensity noise and demonstrate that, when constrained by shot noise, the interferometer can achieve a relative accuracy better than 10^{−11} in measuring Earth's gravitational acceleration. The submicrometer resolution and extended measurement duration offer promising opportunities for exploring fundamental physical laws in new regimes. We discuss two applications well suited for the unique capabilities of the tweezer interferometer: the measurement of gravitational forces and the study of Casimir-Polder forces between atoms and surfaces. Crucially, our proposed tweezer interferometer is within the reach of current technological capabilities.